Biosynthesis of antioxidative enzymes and polyphenolics content in calli cultures of Prunella vulgaris L. in response to auxins and cytokinins - Hina Fazal; Bilal Haider Abbasi; Nisar Ahmad; Bushra Noureen; Jahangir Shah; Dan Ma; Liu Chuanliang; Fazal Akbar; Muhammad Nazir Uddin; Haji Khan; Mohammad Ali (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
Prunella vulgaris L. is one of the therapeutic herbs containing various polyphenolics, which is used for multiple medicinal purposes. In this study, plant growth regulators (PGRs)-induced calli cultures from seed-derived leaf explants were exploited for the production of stress enzymes and polyphenolics. A growth curve was plotted for each PGR for 49 days period, which showed a distinct lag, log and decline phases. Here, the combination of naphthalene acetic acid (NAA) and 6-benzyleadenine (BA; 0.5 and 2.0 mg l−1) produced maximum fresh (6.32 FW-g/100 ml) and dry biomass (0.75 DW-g/100 ml) in contrast to control. The maximum synthesis of SOD (0.0154 FW-nM/min/mg) was detected on media comprising mixture of NAA and BA (1.5 mg l−1), while POD enzyme (0.366 FW-nM/min/mg) was higher at 0.5 mg l−1 NAA and 2, 4-dichlorophenoxy acetic acid. Further, NAA and BA (1.5 and 2.0 mg l−1) boosted up the synthesis of phenolics (18.83 GAE-mg/g-DW) and flavonoids content (18.05 RE-mg/g-DW) than control. Moreover, NAA of 1.0 and 2.0 mg l−1 were found supportive for maximum antioxidant activity (87.4%) and total protein (716 µg BSAE/mg-DW). This study will contribute in the development of cell culture in fermenter and synthesis of antioxidant secondary metabolites for commercial uses.